Evaluation of access and participation plans: Understanding what works - Moores, Elisabeth; Summers, Robert J.; Horton, Matthew; Woodfield, Lizzy; Austen, Liz; Crockford, Julian (Frontiers in Education, 2023)
•Two current policy options are presented to improve evaluation of access and participation work:independent-external evaluation vs. in-house evaluation •Evaluation of access and participation work needs to be well-conducted, objective and widely disseminated regardless of outcome •Independent external evaluation is likely to provide objectivity and the right skills, but providing effective and timely feedback may be prohibitively expensive •Without support, in-house practitioner teams risk lack of objectivity and skills •Neither external nor in-house evaluation is likely to solve issues of publication bias; usage of open science principles could help •Working with academics and experts internal to the institution could provide the skills to work well under the open science framework •Working as a sector to avoid duplication of effort is likely to get us further, faster